An innovative magnetic Ni0.1Co0.9Fe2O4/g-C3N4 nano-micro-spherical heterojunction composite photocatalyst with an extraordinarily prominent visible-light-irradiation degradation performance toward organic pollutants. Issue 28 (7th July 2020) - Ying, Zongrong; Sun, Jing; Lin, Xuemei; Wang, Yuxuan; Hui, Shengjie; Zhang, Yongzheng
Abstract : An ultra-high-performance magnetic heterojunction photocatalyst was fabricated via post co-calcining the mixture of solvothermal micro-spherical g-C3 N4 and nanospherical Ni0.1 Co0.9 Fe2 O4 . Abstract : Environmental pollution removal is attracting more attention these days because of increasing environmental problems. The use of photodegradation catalysts is a promising avenue in resolving environmental issues and therefore high-performance photocatalysts are urgently needed. Herein, we solvothermally synthesized a micro-spherical g-C3 N4 photocatalyst and a nanospherical Ni0.1 Co0.9 Fe2 O4 photocatalyst, and then innovatively employed small amounts of Ni0.1 Co0.9 Fe2 O4 nanospheres coupled with g-C3 N4 microspheres to fabricate a novel magnetic Ni0.1 Co0.9 Fe2 O4 /g-C3 N4 nano-micro-spherical heterojunction photocatalyst through post co-calcination. Various techniques, including scanning electron microscopy, transmission electron microscopy, X-ray diffraction, Fourier transform-infrared spectroscopy and UV-vis diffuse reflectance spectroscopy, were employed to analyze the as-synthesized hybrid photocatalyst. The resultant photocatalyst exhibits a record high photocatalytic degradation activity against methylene blue under visible-light irradiation with a 100% degradation rate within only 10 min, corresponding to an extraordinarily prominent degradation reaction rate constant k value of up to 0.586 min −1 . Our strategy opens a new effective way for fabricating high-performance photocatalysts and our novel Ni0.1 Co0.9 Fe2 O4 /g-C3 N4 heterojunction photocatalyst is of great potential for application in environmental treatments.